The Role of Perceived Security in E-Wallet Adoption Using TAM Among Generation Z - Zuniatami, Azzahra Lintang; Mahardhika, Arya Samudra (Politeknik Piksi Ganesha Indonesia, 2025)
This study aims to empirically examine the acceptance of e-wallet usage among Generation Z in Indonesia using the Technology Acceptance Model (TAM). The model explains how Perceived Ease of Use, Perceived Usefulness, and Perceived Security influence the intention to use e-wallets and the decision to use e-wallets directly. The study employs a quantitative method with primary data as its source. A purposive sampling technique was used to select 264 respondents. Data analysis was conducted using Partial Least Squares (PLS), a Structural Equation Modeling (SEM) approach. The statistical test results indicate that Perceived Ease of Use and Perceived Usefulness significantly influence Intention to Use, Perceived Ease of Use affects Perceived Usefulness, and Intention to Use has a significant effect on Actual Use. However, Perceived Security does not have a significant impact on Intention to Use.